Manajemen Strategik Haji Mabrur Sepanjang Hayat - Abdul Basir; Robingun Suyud El Syam (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This article aims to explore the strategic management of the Mabrur Hajj throughout life, by looking beyond the meaning of experts to produce an in-depth meaning of this theme. This article is a qualitative research finding, using Pierre Bourdieu's habitus theory, and analyzed inductively. The results of the research show: that the term Mabrur Hajj throughout life is not only in the procession during the Hajj on the holy land, but more than that, it must be preserved in life's practices throughout one's life, so management is needed so that the goal of maintaining the Mabrur Hajj title is realized. Management in order to make this happen can be carried out by providing education about strategies for achieving the title of Hajj Mabrur and religious moderation which have been released by the Ministry of Religion, with training, seminars and other guidance. This essence must be reduced in everyday life, throughout life, be consistent in maintaining it so that it becomes a habit. Research implications, further studies on lifelong management of the Mabrur Hajj are needed for a wider reach. Keywords: management; pilgrimage; mabrur; all life.